Adoption of Augmented Reality (AR) in Construction Cost Management: A Preliminary Framework - Azahari, Safiah; Che Haron, Roziha (Research in Management of Technology and Business, 2024)
The integration of Augmented Reality (AR) into construction cost management practices has emerged as a promising technological advancement in the Architecture, Engineering and Construction (AEC) industry. However, despite its potential benefits, there exists a notable gap in understanding the practical application and barriers to implementing AR in this context. Therefore, to bridge this gap, this paper delves into the conceptual foundation of AR to evaluate its potential implementation in construction cost management. This study aims to enlighten others on the significance of innovative construction cost management practices. It will also contribute towards in-depth knowledge of the role of AR in construction cost management.